A proportionate study of cancer mortality among members of a vegetarian society. - Kinlen, L; Hermon, C; Smith, P (1983)
A proportionate study was carried out of the causes of death of the 759 Vegetarian Society members whose deaths were recorded in Society records and whose death certificates could be traced. Compared to the general population, a lower proportion of deaths from respiratory diseases and from lung cancer was noted particularly in long-standing members, consistent with the evidence that vegetarians smoke less than the average. The proportion of deaths from colorectal cancer was slightly lower than in the general population but there was no reduction in the proportions of deaths from other diseases that have been linked with meat or fat consumption, such as cardiovascular diseases and breast cancer. The proportions of deaths from stomach cancer and from accidents and violence were greater than expected. The significance of the findings is discussed and also the possible limitations of the proportionate method of analysis in relation to studies of vegetarians.